Globalization and Education Proceedings of the Joint Working Group, The Pontifical Academy of Sciences, The Pontifical Academy of Social Sciences, 19 - 17 November 2005, Casino Pio IV - Berthélemy, Jean-Claude; Bloom, David E.; Chakrabarti, Manas; Gardner, Howard E.; Hassan, Mohamed H.A; Kumar Menon, M. Govind; Llach, Juan J.; Léna, Pierre; Malinvaud, Edmond; Mitra, Sugata; Mittelstrass, Jürgen; Negroponte, Nicholas; et al. (De Gruyter, 2008)
This book presents the results of a joint meeting organized by the Pontifical Academy of Sciences and the Pontifical Academy of Social Sciences where renowned international scholars discussed the importance of education in an increasingly globalized world. The papers cover a wide range of topics, including immigration, education in developing countries, knowledge transfer, social, economic, cultural, and political conditions in global education, technology, communication, access to information and knowledge, as well as, bio-anthropological issues